2012
DOI: 10.1136/bcr-2012-006800
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in management of complex panic disorder in a palliative care setting

Abstract: SummaryThis is a complex case of post-traumatic stress disorder (PTSD) with comorbid panic disorder occurring in a woman in her mid-60s, with a family history of neurotic illness. PTSD arose in the context of treatment for terminal lung cancer. This patient who had been close to her father watched him die of cancer, when he was about her age. Her diagnosis and treatment prompted traumatic recollections of her father's illness and death that resulted in her voluntary withdrawal from cancer treatment. The goals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…This means that it is effective with PTSD, as well as the anxiety and depression related to psychological traumata (Thinker & Wilson, 1999). EMDR was originally applied to the anxiety associated with traumatic memories (Udo & Gash, 2012). Although EMDR was the primary treatment for PTSD, there has been limited research into EMDR application to children and adolescents with PD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that it is effective with PTSD, as well as the anxiety and depression related to psychological traumata (Thinker & Wilson, 1999). EMDR was originally applied to the anxiety associated with traumatic memories (Udo & Gash, 2012). Although EMDR was the primary treatment for PTSD, there has been limited research into EMDR application to children and adolescents with PD.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, the AIP model is based on the idea that all humans have a physiologically based information processing system that maintains a delicate balance and allows information to be processed to an “adaptive resolution.” It assumes that traumatic experiences can disrupt this information processing system, leaving associated sights, sounds, thoughts, and feelings unprocessed and dysfunctionally stored, and that this may later result in a repeated negative pattern of thinking, feeling, and behaving. Therefore, it is hypothesized that the direct reprocessing with EMDR of these memories of etiological events and other experiential contributors can have a positive effect on the treatment of most clinical complaints (Udo & Gash, 2012; Rimini et al, 2016). The objective of EMDR therapy is to restore the natural information streaming to reach an adaptive resolution (Shapiro, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…55 Finally, even if CBT were effective for PTSD at the end of life, not all patients are willing to participate, perhaps due to a desire to avoid painful or triggering topics. 56 There is some indirect evidence that CBT may benefit the terminally ill having PTSD. Although not tested exclusively at the end of life, CBT is effective with many patients with PTSD 57 and commonly co-occurring conditions, such as pain.…”
Section: Modified Cognitive Behavioral Therapymentioning
confidence: 99%
“…55 Finally, even if CBT were effective for PTSD at the end of life, not all patients are willing to participate, perhaps due to a desire to avoid painful or triggering topics. 56…”
Section: Alternative Therapeutic Approachesmentioning
confidence: 99%
“…Studies have suggested that PTS and PTG are important aspects of how people respond to advanced cancer (Butler et al, 1999;Meisel et al, 2012;Lethborg et al, 2006;Mystakidou et al, 2007). PTS can impact a patient's quality of life (Meisel et al, 2012), level of suicidality (Spencer, Nilsson, Wright, Piri & Prigerson, 2010) and his or her willingness to engage in treatment (Udo & Gash, 2012). PTG serves a protective function at a physiological level (Diaz, Aldridge-Gerry & Spiegel, 2014) and is also related to enhanced quality of life (Tomich & Helgeson, 2004).…”
Section: Study Rationale and Aimsmentioning
confidence: 99%